Expression of glucagon-like peptide-1 and glucose-dependent insulinotropic polypeptide in the rat submandibular gland is influenced by pre- and post-natal high-fat diet exposure - Sangsuriyothai, Pornchanok; Watari, Ippei; Serirukchutarungsee, Saranya; Satrawaha, Sirichom; Podyma-Inoue, Katarzyna Anna; Ono, Takashi (Frontiers in Physiology, 2024)
Background: Incretins, i.e., glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) promote insulin secretion to reduce postprandial blood sugar. Previous studies found incretins in the salivary glands. However, the role of GLP-1 and GIP in the submandibular gland (SMG) is unclear. This study investigated the effects of a high-fat diet (HFD) on the expression of GLP-1 and GIP throughout the development of rat SMG. Methods: Pregnant 11-week-old Wistar rats were divided into two groups: those fed on a standard diet (n=5) and those fed on a HFD (n=5). From day 7 of pregnancy and throughout the lactation period, all the rats were fed on either a chow diet or HFD. The newborns were divided into four subgroups (n=6): standard-diet males (SM), HFD males (HM), standard-diet females (SF), and HFD females (HF). The SMGs of 3-and 10-week-old rats from each subgroup were collected under general anesthesia. Moreover, body weight, food intake, and fasting blood sugar were measured. The mRNA expressions of GLP-1 and GIP were quantified, and their localization was observed using immunohistochemistry (p<0.05). Results: GLP-1 mRNA expression was statistically significantly upregulated in HM than in HF at 3 weeks. Moreover, GLP-1 mRNA expression was significantly higher in HM than in both SM and HF at 10 weeks. Although a decreasing trend was observed in GIP mRNA expression in both 3-and 10-weekold rats fed on a HFD, a significant difference between HM and SM only occurred at 3 weeks. Furthermore, the GIP mRNA expression of HM was lower than that of HF at 10 weeks. Immunohistochemical staining revealed GLP-1 and GIP expressions mainly in the SMG duct system. Moreover, vacuolated cytoplasm in the duct was observed in rats fed on a HFD. Conclusions: Exposure to HFD during pre-and post-natal periods increased GLP-1 mRNA expression in the SMGs of male rats. However, GIP expression decreased following the HFD in male newborns. Furthermore, a decreasing trend of GIP mRNA expression was observed in male newborns after HFD feeding. Sex influenced incretin hormones secretion and obesity-related conditions. HFD during pre-and post-natal periods reprograms the epigenome, contributing to subsequent disease development.